Spatial components in social interaction spaces: a review of Jakarta urban kampongs dwellers - Anggiani, Mona; Arifin, Lilianny Sigit; Dwisusanto, Yohanes Basuki (Universitas Mercu Buana, 2025)
Architecture exists because of the response to the needs of human social relationships. Space is one part of architecture that is very important for use in everyday human life, one of which is social interaction space. Urban kampongs are settlements in Jakarta that contain social interaction space for dwellers. This space is an important space and is often discussed in the scope of architecture, but there has been no special review of the aspects that form the social interaction space used by dwellers of urban kampongs in Jakarta. Therefore, it is important to conduct a special study that discusses the aspects that form the social interaction space in urban kampongs. This study is a literature study that uses a qualitative method with a narrative descriptive analysis approach. The basic literature used is an understanding of spaces from the perspective of sociology, anthropology, and geography. The results of the study show that the social interaction space of dwellers of urban kampongs in Jakarta is greatly influenced by non-physical aspects (socio-cultural) and physical aspects (location). This study is very useful for enriching the theory regarding the social interaction space of urban kampongs in particular and the theory of spatial design in general.